Webinar "Social Ethics Education for Teenagers in the Era of Disinformation at KP Margajayu Senior High School" - Lilis Emalia; Akbar Nur Fadhilah; Adika Riski; Andika Alfaridzi; Agas Ali; Aldirizki Aldirizki; Ariq Fauzan; Andhika Riftan; Yogi Yogi (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
The community service team of academics and students from STMIK Mardira Indonesia has executed a community service initiative at SMA KP Margahayu, focusing on evaluating the necessity of social media ethics education for adolescents and its implementation tactics using a multidimensional framework.  The employed approaches comprised a blend of seminars, practical workshops, and interactive simulations. The research findings demonstrate that incorporating a digital literacy curriculum, interactive training, social campaigns, and collaboration among educational institutions, families, and communities significantly improves knowledge of digital ethics.  The enduring effects encompass enhanced critical thinking abilities, favorable social interactions, and increased safeguarding of digital privacy among adolescents.